2017
DOI: 10.1111/jocn.13911
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experience of the transfer of ICU patients to general wards: A great responsibility and a huge challenge

Abstract: Aims and objectives: The aim of the study was to describe nurses' experiences of patients' transition from ICUs to general wards and their suggestions for improvements.Background: In the ICU, the most seriously ill patients with life-threatening conditions and multiple organ dysfunction syndromes are cared for and carefully monitored by specially trained professionals using advanced techniques for the prevention of failure of vital functions. The transfer of ICU patients to general wards means a change from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
3
45
0
3
Order By: Relevance
“…It is noted that approximately half of the practices and strategies indicated by the studies can negatively influence the quality of the transitions. Among the main barriers are ineffective communication ( 21 , 23 - 25 , 27 , 36 - 38 ) , lack of planning, and choosing the inappropriate time for discharge, both from the point of view of time/day of discharge and the patient’s readiness to be discharged ( 11 , 14 , 19 - 22 , 24 - 25 , 27 - 28 , 30 , 32 - 35 , 37 - 38 , 42 ) . The ideal conditions for patient discharge should consider, in addition to the clinical aspects, their level of dependence, the availability of family support, and the capacity of the destination unit/team to meet their demands ( 28 , 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that approximately half of the practices and strategies indicated by the studies can negatively influence the quality of the transitions. Among the main barriers are ineffective communication ( 21 , 23 - 25 , 27 , 36 - 38 ) , lack of planning, and choosing the inappropriate time for discharge, both from the point of view of time/day of discharge and the patient’s readiness to be discharged ( 11 , 14 , 19 - 22 , 24 - 25 , 27 - 28 , 30 , 32 - 35 , 37 - 38 , 42 ) . The ideal conditions for patient discharge should consider, in addition to the clinical aspects, their level of dependence, the availability of family support, and the capacity of the destination unit/team to meet their demands ( 28 , 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Following a scoping review of the ICU transfer literature, Stelfox and colleagues 6 suggest that a multi-pronged approach is likely necessary to Breengineer^the transfer process and highlight a need for better patient and family engagement within the transfer process. 33,35 A recent qualitative study of perceived barriers and facilitators to high-quality transfer practices reported that ICU providers, ward providers, and patients and families all recommended the use of both communication tools (e.g., standardized written summary of patient course and treatment plan) and employing multimodal communication practices (i.e., verbal, written, electronic) to document the transfer to ensure continuity of care. 36 This was further echoed in our study, with both administrator groups identifying an opportunity to improve transfer practices by providing patients and families with more information and engaging them in the transfer process (e.g., shared decision-making).…”
Section: Discussionmentioning
confidence: 99%
“…Lost or inaccurate information is a well-known problem in clinical handovers both within ICU and during transfers between ICU and other hospital ward units (Blum & Tremper, 2009;Dutra et al, 2018;Enger & Andershed, 2018;Ganz et al, 2015;Zakrison et al, 2016). Incomplete handover is associated with medical errors and inadequate care (McCloskey et al, 2019;Smeulers et al, 2014).…”
Section: Discussionmentioning
confidence: 99%